PENDAMPINGAN BRANDING DAN PACKAGING UNTUK MENINGKATKAN DAYA SAING UMKM KELURAHAN KARYAMULYA CIREBON - Lena Magdalena; Muhammad Hatta; Mesi Febima (STKIP PGRI SITUBONDO, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving economic growth and creating employment opportunities at the local level. However, many MSMEs still face various challenges, particularly in branding and packaging, which are not optimally developed, leading to low competitiveness in an increasingly competitive market. This study aims to provide assistance in branding strategies and packaging design to MSMEs in Karyamulya Subdistrict, Cirebon, to enhance product appeal and expand market reach. The methodology used in this study consists of several stages: identifying problems through surveys and interviews with MSME actors, analyzing branding and packaging needs, and conducting intensive training and mentoring in designing more attractive packaging that aligns with product characteristics. Furthermore, an evaluation was carried out to measure the effectiveness of the assistance by assessing changes in consumer perception and the potential increase in sales after implementing improved branding and packaging strategies. The results of this assistance program indicate an increased understanding among MSME actors regarding the importance of brand identity and packaging as key factors in building customer loyalty and attracting a broader market segment. Additionally, more professional and innovative packaging designs have proven to enhance the visual appeal of products, increasing market penetration opportunities both offline and online. Implementing stronger branding strategies also helps MSMEs establish clearer differentiation amid intensifying industry competition. In conclusion, branding and packaging assistance has positively impacted MSMEs in Karyamulya Subdistrict, Cirebon, by enhancing their competitiveness in the market. It is hoped that similar programs can be replicated in other regions as a solution to support the growth and sustainability of MSMEs in Indonesia.